2022
DOI: 10.1515/cdbme-2022-0033
|View full text |Cite
|
Sign up to set email alerts
|

Segmentation of Circle of Willis from 7T TOF-MRI data and immersive exploration using VR

Abstract: 7T TOF MRI scans provide high resolution images of intracranial vasculature. When segmented, the Circle of Willis is detailed and thus opens up new possibilities, in research but also in education. We propose a segmentation pipeline for the Circle ofWillis, and introduce a prototype that enables exploration of not just the entire Circle of Willis, but also of its centerline, in an immersive VR enviroment. In our prototype, the model can be freely rotated, placed and scaled. A qualitative evaluation was perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…A vesselness filter, thresholding and masking were applied to both datasets in MeVisLab 3.4.2 [ 18 ] to emphasize the vessels. Due to strong variations in vessel size, we found that a combination of multiple vesselness filters worked best [ 19 ]. TOF-MRI data were segmented according to [ 19 ] via thresholding and masking in MeVisLab as well [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A vesselness filter, thresholding and masking were applied to both datasets in MeVisLab 3.4.2 [ 18 ] to emphasize the vessels. Due to strong variations in vessel size, we found that a combination of multiple vesselness filters worked best [ 19 ]. TOF-MRI data were segmented according to [ 19 ] via thresholding and masking in MeVisLab as well [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…Due to strong variations in vessel size, we found that a combination of multiple vesselness filters worked best [ 19 ]. TOF-MRI data were segmented according to [ 19 ] via thresholding and masking in MeVisLab as well [ 20 ]. After editing in Blender 2.93.4 (The Blender Foundation, Amsterdam, Netherlands), to account for fusion artifacts from the segmentation, the Vascular Modelling Toolkit VMTK 1.4.0 [ 21 ] was used to generate centerlines.…”
Section: Methodsmentioning
confidence: 99%
“…In the Circle of Willis context, image segmentation techniques have been applied in neurovascular studies. [48] demonstrated the segmentation of the Circle of Willis from 7T TOF‐MRI data, highlighting the relevance of automated segmentation in neurovascular research. Understanding the Circle of Willis and its variations is crucial for assessing blood flow and vascular‐related pathologies and automated segmentation methods can contribute to this endeavor.…”
Section: Related Workmentioning
confidence: 99%